Pengaruh Pengendalian Internal, Motivasi, Kompensasi Dan Kepemimpinan Terhadap Kinerja Pegawai - Ayu Dwi Puspitasari; Lely Dahlia (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this study was to determine the effect of internal control, motivation, compensation and leadership on employee performance at UPTD Cleanliness District Jatiasih Bekasi. For government organizations, the results of this study are expected to contribute to the implementation of internal control, motivation, compensation and leadership in order to improve the quality of UPTD Cleanliness services and achieve the expected organizational goals.Respondents used in this study were cleaning staff UPTD Cleanliness Jatiasih District Bekasi. Data were collected using interviews, questionnaires, and observations. Descriptive analysis method is used to test the hypothesis and structural modeling with the Partial Least Square application, the SmartPLS program version 3.The results showed that: (1) Internal Control had a significant positive effect on employee performance. (2) Motivation has a significant positive effect on employee performance. (3) compensation does not affect employee performance. (4) Leadership has a significant positive effect on employee performance.